APPLICATION METHODDRILLFORIMPROVINGSKILLSZAPIN DANCE BASIC MOTION IN LEARNING ARTS DANCE CLASS IV SD STATE 165 PEKANBARU - AndellaPutri Andella Putri; Zariul Antosa Zariul Antosa; Erlisnawati Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak :Issues raised in this research is to improve basic motor skills Zapin dance SDN fourth grade students 165 Pekanbaru in learning the art of dance with the application of the method Drill . Learning the art of dance in this school only to learn the material just never did practice immediately . This is due to the lack of teacher knowledge about the art of dance . In belajarpun activities , teachers only use the lecture method or explain the material. In learning the art of dance is done with the lecture method only makes children become passive in learning . So that the formulation of the problem in this research is : " Does the application of the drill method can improve basic motor skills in learning the art of dance Zapin dance fourth grade students of SDN 165 Pekanbaru " . Subjects in this study were 165 fourth grade students of SDN Pekanbaru academic year 2014/2015 the number of students 35 people . This research was conducted in two cycles , cycle I held two meetings with one final assessment cycle and cycle II . These results indicate that the application of the drill method can improve basic motor skills in learning the art of dance Zapin dance fourth grade students of SDN 165 Pekanbaru . In the preliminary data the average value of 31.24 students on the basis of motion assessment Zapin dance in the first cycle of the average value of 66.63 students increased by 35.39 of the results of the initial data . Meanwhile, on the basis of motion assessment Zapin dance second cycle students' average score increased to 76.37 increased by 9.74 of basic motion assessment cycle Zapin dance I. This shows that the application of the drill method can improve basic motor skills of dance zapin in learning dance fourth grade students of SDN 165 Pekanbaru.Keywords : Learning Method Drills, Skills Basic Motion Dance Zapin